Outcome validation report: CCAFS engagement in the Global Commission on Adaptation - Szilagyi, Lili (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
The Global Commission on Adaptation (GCA) was launched in October 2018 to accelerate adaptation action and support by elevating the political visibility of adaptation and focusing on concrete solutions to the climate crisis. It is led by Ban Ki-moon, 8th Secretary-General of the United Nations, Kristalina Georgieva, Managing Director of the International Monetary Fund, and Bill Gates, Co-Chair of the Bill & Melinda Gates Foundation. It is convened by 17 countries and guided by 30 Commissioners, and co-managed by the Global Center on Adaptation and World Resources Institute. The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) has been heavily involved in the work of the GCA. This outcome validation report focuses on how CCAFS has been involved in the GCA processes, focusing on contributions made in 2019.